Awareness and acceptance of teleclinic services during COVID-19 in the general population in Riyadh: Cross-sectional study - Hayat S Alzahrani; Sarah A Alharbi; Yara I Alsadan; Nouf S Alghosn; Sarah M Almazyad; Nowayer Alotaibi; Mohammed Almansour; Khaled K Aldossari; Eyad Demyati; Razan Y Abulreesh (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The first COVID-19 case in Saudi Arabia was reported on March 2, 2020. The Saudi government introduced the "937" service number as one of the telemedicine services for COVID-19 information. Telemedicine uses telecommunication and information technologies in the medical field to deliver healthcare services and improve patients' health status. This study aims to estimate the frequency of teleclinics usage during COVID-19, assess awareness of teleclinics, and assess acceptance of teleclinics during COVID-19 in the Saudi population. MATERIALS AND METHODS: The cross-sectional study used a convenient sample encompassing the 1,583 Saudi and non-Saudi adult population of Riyadh, Saudi Arabia, and was conducted online between August 2020 and April 2021. A self-administrated online questionnaire was distributed to all participants and data were collected on sociodemographics, knowledge of use of teleclinics, and its acceptance. Analysis of quantitative data by t-test and association of qualitative variables by Chi-square test was conducted. Regression analysis was performed on the significant values of univariate analysis. Data were analyzed by SPSS 25. RESULTS: Most (92.5%) participants were female and had a university education (65.9%). The main reason for using teleclinic was experiencing a new complaint (27.3%), next, for medications refill (13.2%), with COVID-19-related issues being the least common reason for using teleclinic (8.2%). The result shows that 77.1% of participants had a good level of acceptance of teleclinic. The regression analysis showed that number of teleclinics utilization, as an advantage it is more convenient, and recommending this service to someone else was significantly associated with acceptance of teleclinics in future. CONCLUSION: As per the findings, the experience of using teleclinic positively impacts the level of acceptance of teleclinic among the population. The adoption of telemedicine for healthcare delivery during the COVID-19 pandemic helped limit the spread of the infection and reduce the risk of exposure to COVID-19 for both patients and healthcare providers. In the future, telemedicine can be used as an alternative to minor complaints and follow-up checkups. In this way, the burden of healthcare system can also be overcome.